Technological Stratigies to Mitigate Insecurity in Nigerian Schools: Implications for Educational Administrators - Walson, Ominini Brother Asako (International Journal on Integrated Education, 2023)
The paper discusses technological strategies to mitigate insecurity in Nigerian schools: implications for educational administrators. The paper observed that there is prevalence of insecurity at all levels of Nigerian educational system which poseS serious threats to human lives and properties.